Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7150/ntno.64790
|View full text |Cite
|
Sign up to set email alerts
|

A 2D nanotheranostic platform based on graphene oxide and phase-change materials for bimodal CT/MR imaging, NIR-activated drug release, and synergistic thermo-chemotherapy

Abstract: Recent years have seen considerable progress in the development of nanomedicine by the advent of 2D nanomaterials serving as ideal platforms to integrate multiple theranostic functions. We synthesized multifunctional stimuli-responsive 2D-based smart nanocomposites (NCs), comprising gold nanoparticles (AuNPs) and superparamagnetic iron oxides (SPIOs) scaffolded within graphene oxide (GO) nanosheets, coated with doxorubicin (DOX)-loaded 1-tetradecanol (TD), and further modified with an alginate (Alg) polymer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…It was observed that the rGO/PEG/ICG nanosystem was sustained for a longer time in in vivo and was capable of targeting tumors. Mirrahimi et al used GO for anchoring superparamagnetic iron oxides (SPIOs) and AuNPs adapted with phase-change material (PCM) for stimulus-based drug release . The study also reveals that the synergistic effect of all, like NIR absorbance of GO, MRI contrast of SPIOs, AuNPs for X-ray attenuation, and PCM for thermosensitive features, make this platform ideally suited for synergistic thermo-chemotherapy in a controllable drug release .…”
Section: Recent Trends Of Nanomaterials In Cancer Theranosticsmentioning
confidence: 99%
“…It was observed that the rGO/PEG/ICG nanosystem was sustained for a longer time in in vivo and was capable of targeting tumors. Mirrahimi et al used GO for anchoring superparamagnetic iron oxides (SPIOs) and AuNPs adapted with phase-change material (PCM) for stimulus-based drug release . The study also reveals that the synergistic effect of all, like NIR absorbance of GO, MRI contrast of SPIOs, AuNPs for X-ray attenuation, and PCM for thermosensitive features, make this platform ideally suited for synergistic thermo-chemotherapy in a controllable drug release .…”
Section: Recent Trends Of Nanomaterials In Cancer Theranosticsmentioning
confidence: 99%
“…Figure 7 E shows a reduction in tumor volume within a few days after PT with DOX-NCs+NIR. Figure 7 F shows the corresponding morphology of tumor and total mice view from pre injection to 90 days of PT [ 119 ].…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
“…Choi et al, Yang et al, Mirrahimi et al, Hong et al, Jia et al, Yang et al, Belu et al, and Lim et al demonstrated multimodal imaging (CLSM, MRI, CT, PET, PAI, RAMAN and ToF-SIMS) and multimodal therapies including chemo, gene, and PTs. Most of these researchers have also given tremendous efforts to improve the therapeutic capabilities by minimizing GNCs concentration, laser wavelengths from the first biological windows to the second biological window, and less laser powers and irradiation times [ 84 , 97 , 107 , 108 , 119 , 120 , 132 , 139 , 145 , 146 ]. Keshav et al, provided excellent pharmacokinetic data to take the material towards preclinical trials.…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
“…Xu designed a multimodal combination therapy based on ultrasound-responsive nanoparticles [33]. Mirrahimi designed a nanotherapy platform that can be used for CT/MR dual imaging and realized DOX release and strong thermochemotherapeutic effects [34]. You developed a nanoplatform modified with Pt (platinum), which acts as a catalyst to continuously break down H 2 O 2 to O 2 and relieve hypoxic photodynamic therapy [35].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutics 2023, 15, x FOR PEER REVIEW 3 of 23 realized DOX release and strong thermochemotherapeutic effects [34]. You developed a nanoplatform modified with Pt (platinum), which acts as a catalyst to continuously break down H2O2 to O2 and relieve hypoxic photodynamic therapy [35].…”
Section: Introductionmentioning
confidence: 99%